MODIFIED LAGUERRE WAVELET BASED GALERKIN METHOD FOR FRACTIONAL AND FRACTIONAL-ORDER DELAY DIFFERENTIAL EQUATIONS - Secer, Aydin; Ozdemir, Neslihan (VINCA INST NUCLEAR SCI, 2019)
The application of modified Laguerre wavelet with respect to the given conditions by Galerkin method to an approximate solution of fractional and fractional-order delay differential equations is studied in this paper. For the concept of fractional derivative is used Caputo sense by using Riemann-Liouville fractional integral operator. The presented method here is tested on several problems. The approximate solutions obtained by presented method are compared with the exact solutions and is shown to be a very efficient and powerful tool for obtaining approximate solutions of fractional and fractional-order delay differential equations. Some tables and figures are presented to reveal the performance of the presented method.
Keywords: Galerkin method; Laguerre wavelet; method of steps; fractional differential equations; fractional-order delay differential equations; APPROXIMATION; Thermodynamics